Pembuatan Daftar Hitam Pemegang Nama Domain Terblokir sebagai Upaya Preventif Hak Cipta di Media Digital - Sitorus, Tiara Agustina; Mayana, Ranti Fauza; Permata, Rika Ratna (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research highlights the problem of copyright infringement through illegal websites, especially in the context of free movie streaming. The purpose of this research is to explain the formulation of creating a blacklist of blocked domain names as a preventive measure in protecting copyright in digital media based on Indonesian positive law, as well as identifying the liability of electronic system organizers related to copyright infringement in ICT media. The method used is normative and comparative juridical with data from various sources. The Safe Harbor concept protects PSEs from liability for copyright infringement on their platforms, but proactive measures are still required. Recommendations include improving monitoring of user content, cooperation with copyright owners, updating internal policies, and disseminating copyright education to users.